Medicinal uses of the Asteraceae family in Zimbabwe: A historical and ecological perspective - Maroyi, Alfred (Ethnobotany Research and Applications, 2023)
Background: Several plant species belonging to the Asteraceae family are widely used as sources of traditional medicines. The current study was aimed at providing a systematic review of ethnomedicinal, phytochemical and pharmacological properties of Asteraceae species used as sources of traditional medicines in Zimbabwe. Methods: Information related to the ethnomedicinal, phytochemical and pharmacological properties of Asteraceae species was systematically collected using relevant keywords from online databases such as BioMed Central, Web of Science, Springerlink, Google Scholar, Scielo, PubMed, Science Direct, ACS Publications, Scopus and JSTOR, books, dissertations, theses, scientific reports and herbarium specimens. Results: This study showed that 50 species are traditionally used to manage human and animal diseases in Zimbabwe. These species are used as traditional medicines against 51 medical conditions, mainly used in the treatment of gastro-intestinal problems (34 use reports) and respiratory problems (28 use reports). Aspilia pluriseta, Baccharoides adoensis, Bidens pilosa, Brachylaena discolor var. rotundata, Dicoma anomala, Erythrocephalum zambesianum, Gymnanthemum amygdalinum, G. coloratum, Helichrysum caespititium, Inula glomerata, Laggera crispata, Linzia glabra, Lopholaena coriifolia, Schkuhria pinnata, Senecio coronatus, S. latifolius and Tagetes minuta have the highest number of medicinal uses. Majority of the documented species are characterized by flavonoids (46.0%), terpenoids (44.0%), tannins (40.0%), alkaloids (34.0%), saponins (26.0%), essential oils (24.0%) and glycosides (20.0%). Conclusions: Further phytochemical and pharmacological studies would be of great interest for assessment of ethnopharmacological properties of Asteraceae species used as sources of traditional medicines. Keywords: Asteraceae, Compositae, herbal medicine, indigenous knowledge, natural compounds, Zimbabwe